Cruel Apprenticeship: National Imaginaries in China’s Operating Rooms (Medicine Anthropology Theory, 2022)
Doctors learn to be doctors through clinical or therapeutic apprenticeships. By following, observing, and being mentored by more experienced physicians, trainees at various stages acquire embodied knowledge, affects, and ethics via both taught and hidden curricula. Previous research has demonstrated how biomedical training reproduces the social authority of scientific knowledge. This research article examines how for Chinese surgeons, apprenticeship not only immerses individuals within the scientific logics and hierarchical norms of biomedicine, but also embeds trainees within scientific imaginaries on a national scale. Drawing on ethnographic fieldwork in a Chinese academic hospital and a surrounding network of community hospitals, I examine how apprenticeship for Chinese surgical trainees extends beyond medical school and residency programmes, both in terms of temporality and geography. I examine how ‘technonational’ narratives, which permeate medical practice in China, impact the affects and ethics embodied by Chinese surgical trainees, and argue that changes in training expectations and the scope of training generates entanglements, dreams, and attachments which are cruel in their optimism. Thus, the therapeutic apprenticeship of Chinese surgical training reveals a ‘cruel apprenticeship’, a framing which encourages further exploration of the political and ethical stakes which permeate medical training and practice.